Outspoken : a manifesto for the twenty-first century - Parr, Adrian; Zabala, Santiago, 1975- (Outspoken (McGill-Queen's University Press), 2023)
"In a world of increasing right-wing populism, global capitalism, and a climate emergency, leading thinkers come together to interrogate the meaning and practice of being outspoken. The violence, nativism, persecution, and social hostilities of the twenty-first century demand a call to order: philosophical and theoretical communities must commit their intellectual resources to confronting and articulating the structures, desires, and resentment driving the dismantling of democratic values. Action in the absence of understanding and political vision devoid of inclusive ideas are all the more vulnerable to taking a reactionary turn. Contributors to this volume challenge the return of fascism, dehumanization of immigrants, distrust of science, intolerance of fair and equitable economic models, and suspicion of inclusive political platforms. All, in their own way, tackle the burning question of how we might reimagine twenty-first-century life in the face of divisive forces. Outspoken includes essays by some of the world's most radical thinkers--Rosi Braidotti, Henry A. Giroux, Amelia Jones, and Slavoj Žižek, among others--who together chart multiple progressive courses for political antagonism and social intervention."--